Topics on pediatric surgery. Teaching supporting aids for medicine students. - Zoe Quintero Delgado; Guillermo Cortiza Orbe; Carlos Cabrera Machado; Berta Fonseca Romero; Sergio Luis González López; Lorenzo Pérez Romano (Medisur)
-